Self‐Propelled Nanoswimmers in Biomedical Sensing - Qianfan Chen; Kang Liang (Advanced Sensor Research, 2023)
Abstract Micro/nanomotors are nano‐devices that can convert energy into power to achieve self‐propulsion. Compared to ordinary nanoparticles, the driving force of nanomotors is their unique advantage. This driving force enables the controllable movement with defined direction and speed, allowing these nanoswimmers to perform more complex functions. Biomarkers are important parameters in clinical medicine and are closely related to disease prediction, diagnosis, and condition monitoring. Existing clinical biomarker monitoring and detection methods often require sophisticated equipment and complex operations. The use of micro/nanomotors is expected to greatly simplify these processes with better sensitivity and reliability. This article introduce the major classes of nanoswimmers based on their sources of energy and driving modes, as well as discuss how nanoswimmers can be used as nanosensors for biomarker detection.